2014
DOI: 10.1007/s10295-014-1429-0
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly methodology for efficient synthesis and scale-up of 2-ethylhexyl-p-methoxycinnamate using Rhizopus oryzae lipase and its biological evaluation

Abstract: Lipase-mediated synthesis of phenolic acid esters is a green and economical alternative to current chemical methods. Octyl methoxycinnamate, an important UVB-absorbing compound, was synthesized by the esterification of p-methoxycinnamic acid with 2-ethyl hexanol using Rhizopus oryzae lipase. A molar ratio of 1:2 of p-methoxycinnamic acid and 2-ethyl hexanol was found to give an optimum yield using cyclo-octane (50 ml) as reaction solvent, at a temperature of 45 °C, and 750 U of lipase, resulting in a yield of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…For instance, p-coumaric acid, one of the major lignocellulosic-derived p-hydroxycinnamic acids [19], is subjected to methylation then esterification with 2-ethylhexanol [20,21]. It is noteworthy that the esterification can be carried out either chemically or enzymatically with lipases [22,23]. The most-described chemical pathway relies on the formation of the acyl chloride and the subsequent reaction with 2-ethylhexanol [24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, p-coumaric acid, one of the major lignocellulosic-derived p-hydroxycinnamic acids [19], is subjected to methylation then esterification with 2-ethylhexanol [20,21]. It is noteworthy that the esterification can be carried out either chemically or enzymatically with lipases [22,23]. The most-described chemical pathway relies on the formation of the acyl chloride and the subsequent reaction with 2-ethylhexanol [24].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the optimal conditions for the lipase-catalyzed synthesis of 2-ethylhexyl salicylate determined by the Neural Power software were a reaction time of 23.1 h, a reaction temperature of 66.5 • C, and an enzyme amount of 881 PLU, and an optimal conversion of 88.2% could be obtained. It has been reported that the synthesis of 2-ethylhexyl-p-methoxycinnamate by immobilized lipase at a temperature of 45 • C and an enzyme amount of 750 U resulted in a yield of 91.3% in 96 h [33]. In other literature, we found that enzyme activity might be inhibited by hydrophilic alcohols such as ethanol [34].…”
Section: Artificial Neural Networkmentioning
confidence: 45%
“…The product of this reaction was a mixture of ferulated mono- and diacylglycerols registered under the trade name SoyScreen as an ingredient used in the manufacture of creams with a filter actively absorbing UVA/UVB radiation [ 63 ]. Lipophilic compounds with UV-absorbing ability were also obtained by enzymatic esterification reaction p -MCA with 2-ethylhexanol developed by two independent teams [ 64 , 65 ]. Biological studies also showed that the obtained ester has higher antioxidant activity than ascorbic acid and the free form of p -MCA, as well as good antimicrobial activity against a number of pathogenic microorganisms [ 65 , 66 ].…”
Section: Enzymatic Modifications Of Methoxylated Derivatives Of Cinnamic Acids With Lipid Moleculesmentioning
confidence: 99%
“…Lipophilic compounds with UV-absorbing ability were also obtained by enzymatic esterification reaction p -MCA with 2-ethylhexanol developed by two independent teams [ 64 , 65 ]. Biological studies also showed that the obtained ester has higher antioxidant activity than ascorbic acid and the free form of p -MCA, as well as good antimicrobial activity against a number of pathogenic microorganisms [ 65 , 66 ]. In 2006, also Weber’s research group reported the results of enzymatic synthesis of long-chain alkyl esters of p -methoxycinnamic acid, which can be used as lipophilic additives with antioxidant activity in food, feed and cosmetic industries [ 67 ].…”
Section: Enzymatic Modifications Of Methoxylated Derivatives Of Cinnamic Acids With Lipid Moleculesmentioning
confidence: 99%